Dual Role Stress And Job Satisfaction In Hospitals: A JD-R Perspective - Surawijaya Bakhtiar Kaslam; Muzakar Isa; Aflit Nuryulia Praswati (PESHUM : Jurnal Pendidikan, Sosial dan Humaniora, 2026)
This narrative review aims to synthesize empirical evidence (2017–2025) on the effects of dual job roles and work stress on hospital employee performance, with burnout and job satisfaction as mediating variables, using the Job Demands–Resources (JD-R) model as a theoretical framework. Literature was identified through Scopus, PubMed, ScienceDirect, and Google Scholar, resulting in 46 eligible studies, including 21 representative articles analyzed in depth. The review employed a narrative design strengthened by systematic synthesis procedures following an adapted PRISMA framework and thematic analysis. The findings indicate that dual job roles and work stress function as high job demands that contribute to role overload and emotional exhaustion. Burnout consistently mediates the relationship between excessive demands and declining performance, including increased risk of medical errors, whereas job satisfaction acts as a protective resource that sustains motivation, resilience, and performance outcomes. Organizational supports, particularly effective leadership and adequate staffing, moderate these relationships. This review highlights the importance of integrating structural and psychological factors in sustaining hospital workforce performance within the JD-R perspective.